New Magnetic States in Nanorings Created by Anisotropy Gradients - Altbir-Drullinsky, D; Allende-Prieto, S; Espejo-Pina, A; Castro-Barrera, M (Elsevier B.V., 2019)
The magnetic energy of nanorings with variable anisotropy along their radius have been studied using analytical calculations and micromagnetic simulations. Based on the geometric characteristics of nanorings, four magnetic states are considered, looking to the relatively lower energy magnetization configuration as a function of anisotropy and geometry. Analytical phase diagrams with these states are presented showing that changes in the anisotropy yield the appearance of new magnetic states, here called meron and knot-like states, appear. Nevertheless, micromagnetic simulations evidence that the knot-like state can be interpreted as a vortex configuration with a magnetization that rotates around the border of the ring. The possibility of obtaining new magnetic states is interesting as from fundamental as from applied viewpoint. © 2019 Elsevier B.V.